Laparoscopic total gastrectomy in gastric cancer: Our experience in 92 cases. Issue 5 (September 2013) - Corcione, Francesco; Pirozzi, Felice; Cuccurullo, Diego; Angelini, Pierluigi; Cimmino, Vincenzo; Settembre, Anna
Abstract: Introduction: Laparoscopic total gastrectomy (LTG) is seldom used for gastric cancer because the complex vascularization and lymphatic drainage makes lymphadenectomy and esophagojejunal anastomosis difficult and requires special skills. Our aim was to demonstrate the feasibility and accuracy of LTG in gastric cancer with D2 lymphadenectomy.Material and methods: Eighty-eight LTG and four laparoscopic remnant gastrectomies (LRGs) were performed over >12 years. The median patient age was 64 years, and the male/female ratio was 1.49/1. Eighty-seven patients had a D2 and only five patients had a D1 lymphadenectomy. We propose the retrospective analysis of intra- and perioperative mortality and morbidity.Results: In only four of 96 cases approached by laparoscopy, a conversion to laparotomy was needed. There were two (2.17%) perioperative deaths in 92 procedures and few complications. Histological data show 79 advanced gastric cancers (AGC), 11 early gastric cancers (EGC), and two gastric diffused lymphomas. The five-year Kaplan-Meier overall survival in patients with EGC and AGC was 100% and 58%, respectively.Conclusions: The results demonstrate the feasibility of an oncologically correct minimally invasive total gastrectomy. We would like to promote comparisons among different institutions to achieve better standardization of indications and techniques for a laparoscopic approach to gastric cancer.